Gender Differences in Precarious Work Settings - C. Young, Marisa (Relations industrielles / Industrial Relations, 2010)
This study uses human capital and gender stratification theory to answer three research questions concerning the gendered patterns of precarious employment, the effects of human capital investments and family obligations on precarious employment, and the extent that these investments and obligations affect precarious employment differently for men and women. Lucrative jobs that offer benefits, union protection, with full-time work status were considered indicators of high quality and therefore non-precarious employment. Using data from U.S. respondents, findings suggest: a) a “gender” to precarious employment in that women are more likely to work in low quality job settings; b) gender discrepancies in benefits and union protection are explained by differences in men’s and women’s human capital, family investments, and other work-related situations; and, c) gender differences in wages and part-time work status result from workplace discrimination towards women. The implications of these findings are discussed along with recommendations for future research.